PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA TERPADU BERORIENTASI PENDIDIKAN KARAKTER PADA MODEL PEMBELAJARAN EXCLUSIVE - Vandan Wiliyanti; Eko Suyanto; Abdurrahman Abdurrahman (Jurnal Pembelajaran Fisika, 2014)
The EXCLUSIVE learning model design as learning program on the theme of nature and around us has never been used by teacher whom leading to character education at the curriculum 2013. To understand the concept of integration of integrated, has developed a learning devices in the form of teacher`s book supplement and student`s book supplement so that the student`s learning process becomes easier, effective, and exciting with applying the scientific approach. The development of teacher`s book supplement and student`s book supplement was started with need analysis and identification of source, identification of product specification will be developed, and then the development of product was in the form of teacher`s book supplement and student`s book supplement. The result of test of the effectiveness of learning devices has been developed showed effective as a learning devices The result of field test, in class VII F SMPN 12 Bandar Lampung showed that the percentage of student`s learning outcome by 87 % complete KKMDesain pembelajaran model EXCLUSIVE sebagai program pembelajaran pada tema “alam dan sekitar kita” belum pernah digunakan oleh guru yang mengarah pendidikan karakter pada kurikulum 2013 ini. Untuk memahami konsep keterpaduan IPA Terpadu, telah dikembangkan perangkat pembelajaran berupa suplemen buku guru dan suplemen buku siswa agar proses belajar siswa menjadi lebih mudah, efektif, dan menarik dengan menerapkan pendekatan Scientific Approach. Pengembangan suplemen buku guru dan suplemen buku siswa diawali dengan analisis kebutuhan dan identifikasi sumber daya, identifikasi spesifikasi produk yang akan dikembangkan, kemudian pengembangan produk berupa suplemen buku guru dan suplemen buku siswa. Hasil uji efektifitas perangkat pembelajaran yang telah dikembangkan menunjukkan efektif sebagai perangkat pembelajaran. Hasil uji lapangan, pada siswa kelas VIIF SMP Negeri 12 Bandar Lampung dengan menunjukkan persentase ketuntasan hasil belajar siswa sebesar 87,00% tuntas KKM.Kata kunci: model pembelajaran exclusive, pendidikan karakter, penelitian pengembangan, perangkat pembelajaran